ANALYSIS OF STUDENTS' SCIENCE LITERACY ABILITY AT SIGI HIGH SCHOOL USING MIXED METHOD APPROACH: IMPLICATIONS OF CONCEPT UNDERSTANDING AND PROBLEM SOLVING IN DAILY LIFE - Esterlina Marpaung, Meida; Fardha, Rizka (CV. Lafadz Jaya, 2024)
This study analyzes the science literacy abilities of students at SMA Negeri 6 Sigi, focusing specifically on chemistry literacy. The objective is to evaluate the extent to which students understand chemistry concepts and can apply them in solving everyday problems. Using a mixed-method approach, qualitative data were collected through a Likert-scale questionnaire, while quantitative data were gathered from a multiple-choice test requiring reasoned responses. Results show that while students self-report high levels of chemistry understanding, their actual performance in applying these concepts is limited, with significant discrepancies observed between perceived and demonstrated abilities. The study highlights the importance of incorporating contextual and inquiry-based learning approaches in chemistry instruction to improve conceptual understanding and reasoning skills. These findings provide valuable insights for educators in enhancing chemistry literacy through real-life applications, ultimately fostering students' critical thinking and problem-solving skills.